Pengaruh Metode Dialog terhadap Maharah Kalam Siswa Kelas VIII SMP Islam Al Bayyinah Makassar - Sri Wahyuni; Fauziah Bachtiar; Mardhiana Jamal (Universitas Palangka Raya, 2026)
This study aims to analyze the effect of the dialogue method on the Arabic speaking skill (maharah kalam) of eighth-grade students at SMP Islam Al Bayyinah Makassar. The research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The sample consisted of 33 students selected through purposive sampling. Data were collected through an oral test on the theme of assafar (travel), which was assessed based on pronunciation, intonation, fluency, and content comprehension. Data were analyzed using descriptive statistics and a paired sample t-test to determine the effectiveness of the dialogue method in improving students’ speaking skills. The results showed an increase in the mean score from 62.27 on the pretest (low category) to 78.33 on the posttest (moderate category). Hypothesis testing revealed a t-value of -7.514 with a significance level of 0.000 (< 0.05), indicating a statistically significant effect of the dialogue method on students’ maharah kalam. These findings demonstrate that the dialogue method is effective in enhancing Arabic speaking skills through interactive, communicative, and student-centered learning. Therefore, the dialogue method can be recommended as an alternative instructional strategy for improving Arabic speaking competence at the junior secondary school level.